The main characteristics of the unemployed in Slovenia - Kavkler, Alenka (Naše gospodarstvo, 2006)
This study analyses the main developments in the labour market in Slovenia. Special attention is paid to the analysis of the duration of unemployment spells based on data obtained from the Employment Office of the Republic of Slovenia. The database consists of the unemployment spells between January 1st, 2002 and November 18th, 2005, with more than 450,000 entries. Different survival analysis techniques are described and the Kaplan-Meier estimates of the survival function are presented. The effects of the factors sex, age and level of education on the duration of unemployment spells are discussed.
Keywords: Slovenia; Slovenija; trg dela; trg delovne sile; unemployment; brezposelnost; ekonomski modeli; ekonomske analize